Implementing the Readiness of Key Audit Matters at Division X KAP ABC - Rahcoyoning Widianingrum; Nureni Wijayati (Interdisciplinary Social Studies, 2022)
Users of financial statements may have higher expectations due to audit reports, which are thought to be of no informational value. Including essential information in the audit report will decide how it can be used because the "expectations gap"—the difference between what users expect and what the auditing profession believes—has risen dramatically over time. This study aims to analyze the readiness to implement Audit Standard SA 701 Key Audit Matters (KAM) at Division X KAP ABC (an Indonesian audit firm) and the auditors' understanding of KAM, including potential doubts regarding the classification of KAMs with other reporting standards such as SA 706 Emphasis of Matter and SA 570 Going Concern. The method of collecting data was through a questionnaire and semi-structured interviews with external auditors in charge at Division X KAP ABC. The questionnaire statements are taken from previous research of Hegazy and Kamareldawla based on paragraphs SA 701, SA 706, and SA 570, which consist of 26 statements. The analysis results conclude that the auditors understand the explanation of SA 701. However, there is potential for doubt in classifying a matter as the Emphasis of a Matter and Going Concern. Concerning the implementation readiness of KAM SA 701 in 2022, Division X KAP ABC has communicated and interacted more with its clients and conducted training and sharing sessions.